2023
DOI: 10.1007/s11010-023-04743-x
|View full text |Cite
|
Sign up to set email alerts
|

GDF15 as a key disease target and biomarker: linking chronic lung diseases and ageing

Abstract: Growth differentiation factor 15 (GDF15), a member of the transforming growth factor-beta superfamily, is expressed in several human organs. In particular, it is highly expressed in the placenta, prostate, and liver. The expression of GDF15 increases under cellular stress and pathological conditions. Although numerous transcription factors directly up-regulate the expression of GDF15, the receptors and downstream mediators of GDF15 signal transduction in most tissues have not yet been determined. Glial cell-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 137 publications
0
13
0
Order By: Relevance
“…The exact function of GDF-15 is still not completely understood; however, it appears to be involved in several cellular processes such as apoptosis, cell repair, and cell development and has a role in the regulation of inflammatory pathways. GDF15 serves as a broad-spectrum biomarker for several diseases, such as cardiovascular, pulmonary, and renal as well as for malignancies [ 15 ]. It has been shown that GDF-15 can modify vascular relaxation and contraction responses in an endothelial-dependent manner that involves the nitric oxide pathway [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The exact function of GDF-15 is still not completely understood; however, it appears to be involved in several cellular processes such as apoptosis, cell repair, and cell development and has a role in the regulation of inflammatory pathways. GDF15 serves as a broad-spectrum biomarker for several diseases, such as cardiovascular, pulmonary, and renal as well as for malignancies [ 15 ]. It has been shown that GDF-15 can modify vascular relaxation and contraction responses in an endothelial-dependent manner that involves the nitric oxide pathway [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been recently shown that EASIX can serve as a predictive marker for both complement activation and overall survival in patients with GvHD and HSCT-TMA [ 12 ]. soluble urokinase plasminogen activator receptor (suPAR) and growth differentiation factor-15 (GDF-15) have been determined as endothelial injury indices in various clinical settings in both hematological and non-hematological diseases [ 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…As well as having specific immunoregulatory roles, in the neonatal setting or relevant animal models, these proteins are associated with several comorbidities and developmental consequences of preterm birth. These include lung development and disease such as BPD [55][56][57][58][59][60][61][62][63][64][65][66][67], in utero and postnatal growth failure [68][69][70][71], HCA [7,72,73], patent ductus arteriosus [74][75][76][77], retinopathy of prematurity [78][79][80][81][82], NEC [83][84][85], hyperglycaemia [86], sepsis [85,[87][88][89][90], brain injury [32,[91][92][93][94], and neurodevelopmental outcomes [95][96][97][98]…”
Section: Associations Between Birth Ga and Episcoresmentioning
confidence: 99%
“…Despite its bad reputation as all-cause mortality marker, increased GDF-15 expression has also been discussed as a survival response [11]. Accordingly, GDF-15 is produced by various cell types during acute tissue injury and was described as prominent senescence-associated secretory phenotype (SASP) factor in senescent cells [12]. Although transient senescence is considered as beneficial in terms of tissue remodelling and repair, chronic accumulation of senescent cells in cartilage or other tissues contributes to progressive degeneration and dysfunction due to the excessive secretion of catabolic and pro-inflammatory SASP factors [13, 14].…”
Section: Introductionmentioning
confidence: 99%